Peran Guru Bimbingan dan Konseling dalam Mencegah dan Mengatasi Perilaku Menyimpang Siswa di Sekolah - Ifnaldi Ifnaldi (Neolectura, 2022)
Guidance and counseling services in schools are directed at achieving educational goals and the objectives of counseling implementation. The preventive function is the guidance and counseling function related to the counselor's efforts to always anticipate various problems that may occur and try to prevent them, so that they are not experienced by students. The reality is that deviant actions can occur anywhere, both in traditional societies, villages, cities and in modern societies whose lives are already modern. This study used literature research. Data collection is carried out by collecting several literature by grouping them into primary data sources and secondary data. Further the collected literature is analyzed using content analysis. The results of the research revealed that to prevent the occurrence of deviant behavior in schools, the role of a teacher who deals specifically with deviant student behavior is needed, in this case it is a counseling guidance teacher